MY legalis management system add on dashboard features / Muhammad Khairul Faizi Mohd Nawi - Mohd Nawi, Muhammad Khairul Faizi (2017)
Messrs. Mansur & Yazrudin business process is currently doing manual filing system. There are many problems that encountered by the stakeholder with current system. The problems are staff need to manually keeping track of progress, no proper system to retrieve legal case information, and information of legal case is offline. The aim for the project is to develop an online dashboard legal case management system for Messrs. Mansur & Yazrudin. There is discussion about the Malaysia legal system, Law firm, Web Application, Dashboard, related works and methodologies in chapter two to gather the understanding of related topics. Based on the literature review, the proposed system will have developed using the Eclipse IDE with MySQL database that based on Waterfall model. There are explanations of each phases and activities of Waterfall model to achieve the aim of the project in the chapter three. There are only three phases of the Waterfall model which requirement analysis, design and development. There limitations of the project are the system does not provide any function for litigation cases, and dashboard only provide several shortcuts. The future works that can be done to improve the system of the project is add the function of litigation case, system dashboard feature can be expanded to the billing, and the system can be deploy to online server.